Engineering personalized instruction in the classroom - Keller, Fred S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A method o f teaching elementary psychology developed at the University of Brasilia and Arizona State University. The content of the course is divided into ten units, which the student completes in individually and at his own pace. The student is tested at the end of each unit and must score a 100 percent correct before passing on the next unit. The results of each test are discussed individually with the student by a proctor, who is another student who has previously taken the course. This one-to-one relationship may be the most import part of the success of this method. A comparison of results on a mid-term examination between Arizona State University students and students from Columbia University is presented.